1990
DOI: 10.1021/bi00482a008
|View full text |Cite
|
Sign up to set email alerts
|

Absorption and fluorescence spectroscopic studies of the calcium-dependent lipid binding protein P36: The annexin repeat as the calcium binding site

Abstract: The existence of a single tryptophan residue in the protein p36, a member of a recently characterized family of Ca2+ binding proteins called annexins, is exploited to provide unique spectroscopic information on the annexin repeat motif and its role in Ca2+ binding. The differences in ultraviolet absorption and fluorescence excitation upon Ca2+ binding are interpreted solely in terms of this tryptophan, which, in view of the pronounced blue-shifts and the presence of vibronic structure, seems to reside in a hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0

Year Published

1990
1990
2000
2000

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 47 publications
3
25
0
Order By: Relevance
“…Corrected Mutations in these amino acids eliminate or significantly alter the characteristic blue shift in the fluorescence emission of the unique tryptophan (Trp212) in annexin 11, which is usually induced upon Ca2+ binding to wild-type annexin 11. Energy transfer experiments could locate the Ca2 +-binding site which is responsible for this blue-shift to within 0.8 nm of Trp212 (Marriott et al, 1990). Based on these observations, we concluded that Gly206 and Thr207 are indeed part of the Ca2+ site whose occupation alters the spectroscopic properties of Trp212.…”
Section: Spectroscopymentioning
confidence: 64%
See 2 more Smart Citations
“…Corrected Mutations in these amino acids eliminate or significantly alter the characteristic blue shift in the fluorescence emission of the unique tryptophan (Trp212) in annexin 11, which is usually induced upon Ca2+ binding to wild-type annexin 11. Energy transfer experiments could locate the Ca2 +-binding site which is responsible for this blue-shift to within 0.8 nm of Trp212 (Marriott et al, 1990). Based on these observations, we concluded that Gly206 and Thr207 are indeed part of the Ca2+ site whose occupation alters the spectroscopic properties of Trp212.…”
Section: Spectroscopymentioning
confidence: 64%
“…Most likely this is a consequence of the amino acid replacement itself. The Glu -+ Ala substitution at steady-state fluorescence emission spectra were recorded as described (Marriott et al, 1990) on an SLM model 8000 spectrofluorometer (Urbana, IL) with the excitation wavelength set at 295 nm and a protein concentration of 0.5-1 mg/ml. Spectroscopic analysis was carried out in spectra buffer (20 mM imidazole/HCl, pH 7.5, 100 mM NaC1, 2 mM NaN,, 1 mM dithiothreitol, 20 pM EGTA) containing varying Ca2 ' concentrations which were adjusted by the addition of CaC1, from appropriate stock solutions.…”
Section: Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation
“…We have also generated a refolded recombinant version of human annexin II that retains key features characteristic of native protein. Spectroscopic analysis of renatured annexin II protein revealed the characteristic calcium-induced blue-shift in tryptophan fluorescence (Marriott et al, 1990) (data not shown), indicating that our recombinant version binds calcium. Refolded annexin II also displayed the well-described ability to bind and cosediment with phosphatidylserine liposomes in the presence of calcium, demonstrating that the recombinant protein retains its ability to bind negatively charged phospholipids (data not shown).…”
Section: Viral Surface Annexin II Is Dispensable For Hcmv Entry Into mentioning
confidence: 92%
“…The physico-chemical properties of renatured recombinant annexin II were tested by measuring the change in tryptophan fluorescence after calcium binding and calciumdependent phospholipid binding. In brief, the fluorescence emission spectrum of a 5 µM solution of annexin II was measured in the presence and absence of 1 mM calcium as previously described (Marriott et al, 1990). Additionally, refolded annexin II was used in liposome cosedimentation experiments as described (Blackwood & Ernst, 1990).…”
Section: Author For Correspondence : Teresa Comptonmentioning
confidence: 99%